The Economic Impact of Merapi Volcano Eruption in Livestock Farming Systems - Atien Priyanti; Nyak Ilham (Indonesian Center for Animal Research and Development, 2011)
Merapi volcano eruption has impact significantly to the most of surrounding farming areas, including livestock, which belongs to rural peoples as the main sources of income. Estimated loss of economic values of resources amounted to IDR 5821 billion, covering among others: salak pondok, farm animals (dairy, beef cattle, buffaloes, sheep, goats and poultry) and food crops (maize and rice field) business. The areas mostly hit by the eruption include the districts of Boyolali, Klaten and Magelang of Central Java, and District of Sleman in DIY. Livestock sub sector of the economy in these areas suffers losses in terms of death of animals, sold and unsold animals, fodder crops, and reduced of milk production. It has been estimated that these losses have reached IDR 88,320 billion. Rehabilitation and reconstruction programs are necessary for both short and longer terms efforts to recover people livelihood which derived particularly from livestock farming. Key words: Economic impact, Merapi eruption, livestock farming